Characterization of the complete plastid genome of Abies forrestii (Pinaceae) from southwest China. Issue 9 (2nd September 2021) - Dong, Na-Lin; Wang, Wei; Wang, Zhao; Zhang, Yuan-Yuan; Shao, Yi-Zhen; Sun, Hong-Ze
Abstract: Abies forrestii is endemic to southwest China and ecologically important as a major component of the cold temperate forests. This study was the first report complete chloroplast (cp) genome of A. forrestii . The complete chloroplast genome was 120, 022 bp in size. In total, 114 genes were identified, including 68 peptide-encoding genes, 35 tRNA genes, four rRNA genes, six open reading frames and one pseudogene. Thirteen genes contain introns. In phylogenetic analysis, A. forrestii was found to be closely related with A. nukiangensis, A. fanjingshanensis and A. delavayi subsp. fansipanensis . Our study will provide potential genetic resources for further evolutionary studies of this ecologically important species.